Armstrong's handbook of human resource management practice : a guide to the theory and practice of people management - Armstrong, Michael, 1928-; Taylor, Stephen, 1965- (London ; New York : Kogan Page, 2026)
Armstrong's Handbook of Human Resource Management Practice by Michael Armstrong and Stephen Taylor is a leading HRM textbook for undergraduate and postgraduate students, as well as professionals studying for CIPD Level 5 and Level 7 qualifications. Fully aligned with the CIPD Profession Map, this updated 17th edition supports modules in human resource management, employment law and people management. Covering core HR areas including employee relations, learning and development, performance management, reward and talent management, this comprehensive edition also develops essential professional skills such as leadership, conflict management, interviewing and statistical analysis. Updated content explores artificial intelligence in HR, systems thinking, hybrid working, employee wellbeing and the evolving balance of hard and soft HR skills.
Armstrongova příručka řízení lidských zdrojů poskytuje komplexní přehled teorie i praxe personálního managementu. Pokrývá klíčové oblasti, jako jsou pracovní vztahy, řízení výkonu, odměňování, rozvoj zaměstnanců či talent management, a zároveň rozvíjí profesní dovednosti včetně leadershipu, zvládání konfliktů či výběru zaměstnanců. Aktualizované vydání reflektuje současné trendy, jako je využití umělé inteligence v HR, hybridní práce a wellbeing zaměstnanců.
"First published in 1977 as A Handbook of Personnel Management Practice by Kogan Page"—Rub titulní stránky
"Seventh edition published in 1999 as A Handbook of Human Resource Management Practice"—Rub titulní stránky
"Eleventh edition published in 2009 as Armstrong’s Handbook of Human Resource Management Practice"—Rub titulní stránky
Obsahuje bibliografické odkazy a rejstříky
Keywords: personální management; přijímací řízení; řízení pracovního výkonu; pracovní podmínky; příručky; učebnice vysokých škol; personnel management; employee selection; performance management; working conditions; handbooks and manuals; textbooks (higher)